Synthesis and characterization of some Lanthanide (III) Ions complexes with Anthranilic-acid and Amino acid phenylalanine - A M.ALHaideri (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2005)
This paper presents the synthesis and identification of some complexes of the (Anthranilic acid )(ligand) symbolized as (A) and some trivalent ions Ln111[ La(III), Ce(I) , Pr(III) , Nd(III) .Gd(III) , Ho (III) and the same ions with the (Phenylalanine ) (ligand) symbolized as Phe). Productsi have been found to be solid crystalline, complexes which have been studied and characterized by the :Thermal stability, solubility, molar conductivity, elemental analysis (C.H.N), magnetic measurements. determination the percentage of the metal in the complexes by (A. A. S) and sepectrosopis methods (Uv-Vis ,IR(. From the above investigations, the general formula has been suggested [M(A-1)3] and M(Phe.1)3] were M111- La(III), Ce(III) , Pr(III) , Nd(III),Gd(III), Ho(III) A-11= C7H6NO2, Phe-11=C9H10NO2.